Impact of Daily versus Weekly Supply of Locally Produced Ready-to-Use Food on Growth of Moderately Wasted Children on Nias Island, Indonesia. (27th February 2013) - Purwestri, Ratna Chrismiari; Scherbaum, Veronika; Inayati, Dyah Ayu; Wirawan, Nia Novita; Suryantan, Julia; Bloem, Maurice Alexander; Pangaribuan, Rosnani Verba; Stuetz, Wolfgang; Hoffmann, Volker; Qaim, Matin; Biesalski, Hans Konrad; Bellows, Anne Camilla
Abstract : This study reports the outcomes of daily (semi-urban areas) and weekly (remote rural regions) programs for moderately wasted children supplemented with locally produced ready-to-use foods in the form of fortified cereal/nut/legume-based biscuits on Nias Island, Indonesia (RUF-Nias biscuit). Thirty-four children in daily and twenty children in weekly programs aged ≥6 to <60 months with weight-for-heightz -score (WHZ) ≥ −3 to < −2 SD were recruited (October 2007–June 2008) on Nias and admitted into existing nutrition centers in the Church World Service project area. Individual discharge criterion was WHZ ≥ −1.5 SD. Weight gain of the children in daily and weekly programs was3.9 ± 3.8 and2.0 ± 2.0  g/kg/day, respectively. A higher proportion of children in daily than weekly programs reached target WHZ (76% vs. 35%, P = 0.004 ). Weight gain at program discharge/closure was highly predicted (R 2 = 0.228, P < 0.001 ) by compliance to RUF biscuits: high vs. low compliance resulted in a 1.33 (95% CI 0.16 to 1.53) g/kg/day higher weight gain. Compliance and admission in daily programs were significant factors in reducing the risk of not reaching the discharge criterion. However, mothers complained more frequently about time constraints in the daily relative to weekly programs.